2009
DOI: 10.1254/jphs.09100fp
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence of Atherosclerosis Progression Mediated by Increased Oxidative Stress in Apolipoprotein E–Deficient Spontaneously Hyperlipidemic Mice Exposed to Chronic Cigarette Smoke

Abstract: Abstract. Cigarette smoking is a major risk factor for cardiovascular disease. The induction of oxidative stress by smoking plays a key role in the progression of atherosclerosis. However, the underlying mechanisms are not fully understood. In the present study, we investigated whether long-term smoking can accelerate the progression of atherosclerosis and whether oxidative stress is implicated in its pathogenesis. Apolipoprotein E-deficient spontaneously hyperlipidemic mice, a model of atherosclerosis, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 49 publications
0
35
0
5
Order By: Relevance
“…The mainstream exposure to cigarette smoke is equivalent to the active smoking, which is composed of about 8% of tar and 92% of gaseous components that contain or induce the formation of ROS (SMITH; FISCHER, 2001). The exposure to cigarette smoke affects a wide variety of oxidizing compounds, such as ROS, which promotes the oxidation of lipids of the cell membrane and increases the systemic oxidative stress (KUNITOMO et al, 2009). Lipid peroxidation leads to a decrease in the membrane fluidity and alignment of receivers, which interferes in the transport and provokes rupture and cell lysis (MACHLIN;BANDICH, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mainstream exposure to cigarette smoke is equivalent to the active smoking, which is composed of about 8% of tar and 92% of gaseous components that contain or induce the formation of ROS (SMITH; FISCHER, 2001). The exposure to cigarette smoke affects a wide variety of oxidizing compounds, such as ROS, which promotes the oxidation of lipids of the cell membrane and increases the systemic oxidative stress (KUNITOMO et al, 2009). Lipid peroxidation leads to a decrease in the membrane fluidity and alignment of receivers, which interferes in the transport and provokes rupture and cell lysis (MACHLIN;BANDICH, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to cigarette smoke affects a wide variety of oxidizing compounds, such as ROS, which promotes the oxidation of lipids of the cell membrane and increases the systemic oxidative stress (KUNITOMO et al, 2009). Lipid peroxidation leads to a decrease in the membrane fluidity and alignment of receivers, which interferes in the transport and provokes rupture and cell lysis (MACHLIN;BANDICH, 1987). One of the first implications of aggression to the blood vessels is the oxidative modification of low-density lipoprotein (LDLc), which can promote the development of atherosclerosis from the endothelial dysfunction with subsequent formation of foam cells and complex plaques composed of necrotic cellular debris, lipid and fibrous tissue (TINKEL et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of vascular cell adhesion molecule-1 (VCAM-1), a member of the immunoglobulin superfamily of CAMs, is increasingly described as the key factor in monocyte infiltration (Nakashima et al, 1998;Truskey et al, 1999). ApoE-knockout mice (apoE KO) have been extensively used to study the relation of hypercholesterolemia and lipoprotein oxidation to atherogenesis Yang et al, 2009;Kunitomo et al, 2009). ApoE-deficient mice have elevated VCAM-1 in aortic lesions (Nakashima et al, 1998), which enhances monocyte recruitment and adhesion (Ramos & Partridge, 2005), while apoE expression in the artery wall reduces early foam cell lesion formation (Hasty et al, 1999).…”
Section: Apolipoprotein E Inflammation and Atherosclerosismentioning
confidence: 99%
“…These and other findings suggest that inflammation is a primary process for atherosclerosis (Ziccardi et al, 2002;RodriguezMoran et al, 2003). Although high dietary intake of the anti-oxidant vitamin E and C has been associated with reduced risk of cardiovascular disease (CVD), well powered clinical trials in atherosclerosis-related CVD have indicated that supplements with vitamin C or vitamin E alone do not provide sufficient benefit, in comparison to, for example, statins (Kunitomo et al, 2009). Furthermore, specific antioxidants scavenge or metabolize some, but not all of the relevant oxidized molecules (Stocker and Keaney, 2004).…”
Section: Animal Models and Strategies For Atherosclerosis Studymentioning
confidence: 99%